COMMUNITY EMPOWERMENT BASED ON TURATS TRADITION: A STUDY OF THE NGAJI KITAB GATHERING ON WAGE THURSDAY NIGHT AT MIFTAHUL ULUM ISLAMIC BOARDING SCHOOL PROBOLINGGO - Mukarromah, Nafilatul; Aisyah, Siti; Khairul Anam, Rifqi (As-Sulthan Journal of Education, 2026)
This study investigates the manifestation of community empowerment rooted in the living turats tradition through the Ngaji Kitab gathering on Wage Thursday Nights at Miftahul Ulum Islamic Boarding School, Probolinggo. This initiative emerged as an existential response to the community's yearning for deeper and structured religious understanding, particularly in fiqh and akhlak derived from the Kitab Kuning. Employing a qualitative-descriptive approach with a sociology of ereignis orientation, the research involves immersive observation, informal interviews, and documentation to capture the congregation's lived experience. The findings reveal that the Sullam Taufiq gathering is not merely a routine, but a moment of disclosure where the transmission of wisdom occurs through communicative methods, local vernacular, and concrete analogies that bridge classical texts with daily life. The resonance of this activity extends to strengthening social cohesion and empowering micro-economies, underscoring that the turats tradition holds vital potential as a medium for shaping religious literacy and cementing the social fabric of rural communities.